Bridging gaps in awareness of cancer associated lifestyle factors in adolescents and young adults: an interventional study in Chandigarh - Singla, Heena; Puri, Sonia; Kumar Sharma, Manoj (International Journal Of Community Medicine And Public Health, 2024)
Background: Cancer is a major public health concern and its incidence is growing worldwide. Adolescent and young adult (AYA) age group is a bridge between paediatric and adult age groups. AYAs have unique lifestyle patterns that may contribute to cancer risk. The study sought to assess the awareness and educate AYAs of Panjab University, Chandigarh about cancer risk associated lifestyle factors. Methods: This cross-sectional Interventional study was conducted from March -June 2023. A predesigned, pretested, validated questionnaire was used for data collection. Descriptive and analytical analysis was performed using SPSS, analytical analysis was conducted using Chi square test to find the relationship between different lifestyle factors and demographic characteristics such as age and gender. Results: The study included a total of 360 participants, consisting of 170 (47.2%) males and 190 (52.8%) females, aged between 15 and 39 years, of Panjab University, Chandigarh. Among them, 92.5% had awareness of smoking as risk factor for cancer. However, lower levels of awareness regarding lifestyle behaviours associated with cancer risk, including inadequate consumption of fruits and vegetables, regular intake of sweets and sugary drinks, following a high-fat diet (28.3%); insufficient physical activity (38.3%) and obesity (36.1%). Conclusions: The current study indicated a disparity in knowledge levels among adolescents and young adults (AYAs) of Panjab University. It is crucial to address the gaps in knowledge and promote healthy behaviours related to cancer prevention through targeted education campaigns among adolescents and young adults.